Hexokinase 2 Depletion Confers Sensitization to Metformin and Inhibits Glycolysis in Lung Squamous Cell Carcinoma - Guo, Wenzheng; Kuang, Yanbin; Wu, Jingjing; Wen, Donghua; Zhou, Aiping; Liao, Yueling; Song, Hongyong; Xu, Dongliang; Wang, Tong; Jing, Bo; Li, Kaimi; Hu, Min; et al. (Frontiers in Oncology, 2020)
Lung squamous cell carcinomas (SCCs) are highly aggressive tumors, and there is currently no effective targeted therapy owing to the lack of specific mutation targets. Compared with lung adenocarcinoma (ADCs), lung SCCs reportedly utilized higher levels of glucose metabolism to meet the anabolic and catabolic needs required to sustain rapid tumor growth. Hexokinase 2 (HK2) is an enzyme that catalyzes the rate-limit and first committed step in glucose metabolism. Here, we investigated the expression and effect of HK2 in lung SCCs. We found a significantly higher HK2 expression in lung SCCs, but not lung ADC or normal tissues. HK2 depletion or inhibition decreased the glycolysis and tumor growth via activating AMPK signaling pathway, which downregulated mTORC1 activity. Furthermore, we found an increased oxygen respiration rate compensating for HK2 depletion. Thus, metformin treatment showed combinatorial therapeutic value, which resulted in greater induction of lung SCC apoptosis in vitro and in vivo. Our study suggests that HK2 depletion in combination with metformin might be a novel effective strategy for lung SCCs therapy.